Use of Pyracantha coccinea Roem. as a possible biomonitor for the selected heavy metals - Akguc, N.; Ozyigit, I. I.; Yasar, U.; Leblebici, Z.; Yarci, C. (Springer, 2010)
In this study, copper, iron, manganese and nickel levels of branches and leaves of Pyracantha coccinea Roem. (firethorn) were measured for determining the heavy metal pollution in Mugla Province. Plant samples were collected from 34 different localities in four different areas of Mugla Province, during 2006 vegetation period. Unwashed and washed leaf samples and unwashed branch samples were subjected to analysis and copper, iron, manganese and nickel concentrations of samples were measured by inductively coupled plasma optical emission spectrometry. The obtained data were analyzed with statistical package for the social sciences statistics program. As a result of measurements, the highest average and lowest values and their collected stations were as follows; the highest average (5.89 +/- 0.04 mu g/g dw) and the lowest (5.20 +/- 0.03 mu g/g dw) values of copper were measured near highways. The average highest iron value (9.53 +/- 1.68 mu g/g dw) was in industrial area while the lowest was near highways (1.73 +/- 0.54 mu g/g dw). The highest value of magnesium accumulation (1.00 + 0.16 mu g/gdw) was measured near highways. The lowest value was determined in urban area (0.40 +/- 0.14 mu g/g dw). The average highest level of nickel was in industrial area while the lowest was determined in urban area. The values were 14.34 +/- 1.59 mu g/g and 4.05 +/- 0.51 mu g/g dw. As a result, it was proven that P. coccinea could be used as a biomonitor species for some of these heavy metals especially for copper and nickel.
Keywords: Biomonitor; Firethorn; Heavy Metal; Mugla